A Self-Stabilizing Hashed Patricia Trie - Knollmann, Till; Scheideler, Christian (Proceedings of the 20th International Symposium on Stabilization, Safety, and Security of Distributed Systems (SSS))
While a lot of research in distributed computing has covered solutions for self-stabilizing computing and topologies, there is far less work on self-stabilization for distributed data structures. Considering crashing peers in peer-to-peer networks, it should not be taken for granted that a distributed data structure remains intact. In this work, we present a self-stabilizing protocol for a distributed data structure called the hashed Patricia Trie (Kniesburges and Scheideler WALCOM'11) that enables efficient prefix search on a set of keys. The data structure has a wide area of applications including string matching problems while offering low overhead and efficient operations when embedded on top of a distributed hash table. Especially, longest prefix matching for $x$ can be done in $\mathcal{O}(\log |x|)$ hash table read accesses. We show how to maintain the structure in a self-stabilizing way. Our protocol assures low overhead in a legal state and a total (asymptotically optimal) memory demand of $Θ(d)$ bits, where $d$ is the number of bits needed for storing all keys.
Keywords: Self-Stabilizing; Prefix Search; Distributed Data Structure

The Traveling Reviewer Problem - Exploring the Relationship Between Offline Locations and Online Rating Behavior - Neumann, Jürgen; Gutt, Dominik; Kundisch, Dennis (Workshop on IS Design and Economic Behavior (ISDEB))

Competitive Routing in Hybrid Communication Networks - Jung, Daniel; Kolb, Christina; Scheideler, Christian; Sundermeier, Jannik (Proceedings of the 14th International Symposium on Algorithms and Experiments for Wireless Networks (ALGOSENSORS))
Routing is a challenging problem for wireless ad hoc networks, especially when the nodes are mobile and spread so widely that in most cases multiple hops are needed to route a message from one node to another. In fact, it is known that any online routing protocol has a poor performance in the worst case, in a sense that there is a distribution of nodes resulting in bad routing paths for that protocol, even if the nodes know their geographic positions and the geographic position of the destination of a message is known. The reason for that is that radio holes in the ad hoc network may require messages to take long detours in order to get to a destination, which are hard to find in an online fashion. In this paper, we assume that the wireless ad hoc network can make limited use of long-range links provided by a global communication infrastructure like a cellular infrastructure or a satellite in order to compute an abstraction of the wireless ad hoc network that allows the messages to be sent along near-shortest paths in the ad hoc network. We present distributed algorithms that compute an abstraction of the ad hoc network in $\mathcal{O}\left(\log ^2 n\right)$ time using long-range links, which results in $c$-competitive routing paths between any two nodes of the ad hoc network for some constant $c$ if the convex hulls of the radio holes do not intersect. We also show that the storage needed for the abstraction just depends on the number and size of the radio holes in the wireless ad hoc network and is independent on the total number of nodes, and this information just has to be known to a few nodes for the routing to work.
Keywords: greedy routing; ad hoc networks; convex hulls; c-competitiveness

The Generalized Nash Bargaining Solution for Transfer Price Negotiations under Incomplete Information - Haake, Claus-Jochen; Recker, Sonja (Group Decision and Negotiation)
In our model two divisions negotiate over type-dependent contracts to determine an intrafirm transfer price for an intermediate product. Since the upstream division's (seller's) costs and downstream division's (buyer's) revenues are supposed to be private information, we formally consider cooperative bargaining problems under incomplete information. This means that the two divisions consider allocations of expected utility generated by mechanisms that satisfy (interim) individual rationality, incentive compatibility and/or ex post efficiency. Assuming two possible types for buyer and seller each, we first establish that the bargaining problem is regular, regardless whether or not incentive and/or efficiency constraints are imposed. This allows us to apply the generalized Nash bargaining solution to determine fair transfer payments and transfer quantities. In particular, the generalized Nash bargaining solution tries to balance divisional profits, while incentive constraints are still in place. In that sense a fair profit division is generated. Furthermore, by means of illustrative examples we derive general properties of this solution for the transfer pricing problem and compare the model developed here with the models existing in the literature. We demonstrate that there is a tradeoff between ex post efficiency and fairness.

Brief Announcement: Competitive Routing in Hybrid Communication Networks - Jung, Daniel; Kolb, Christina; Scheideler, Christian; Sundermeier, Jannik (Proceedings of the 30th on Symposium on Parallelism in Algorithms and Architectures (SPAA))

An Extended Perspective of Technology Pivots in Software Startups: Towards a Theoretical Model - Bohn, Nicolai; Kundisch, Dennis (Proceedings of the 39th International Conference on Information Systems (ICIS))

Determinants of Equilibrium Selection in Network Formation - An Experiment - Hoyer, Britta; Rosenkranz, Stephanie (Games)

Brief Announcement: Communication in Systems of Home Based Mobile Agents - Meyer auf der Heide, Friedhelm; Schaefer, Johannes Sebastian (Proceedings of the 30th on Symposium on Parallelism in Algorithms and Architectures - SPAA '18)

NLP in OTF Computing: Current Approaches and Open Challenges - Bäumer, Frederik Simon; Geierhos, Michaela (Proceedings of the 24th International Conference on Information and Software Technologies (ICIST 2018))
On-The-Fly Computing is the vision of covering software needs of end users by fully-automatic compositions of existing software services. End users will receive so-called service compositions tailored to their very individual needs, based on natural language software descriptions. This everyday language may contain inaccuracies and incompleteness, which are well-known challenges in requirements engineering. In addition to existing approaches that try to automatically identify and correct these deficits, there are also new trends to involve users more in the elaboration and refinement process. In this paper, we present the relevant state of the art in the field of automated detection and compensation of multiple inaccuracies in natural language service descriptions and name open challenges needed to be tackled in NL-based software service composition.
Keywords: Inaccuracy detection; Natural language software requirements

Self-stabilizing Overlays for high-dimensional Monotonic Searchability - Feldmann, Michael; Kolb, Christina; Scheideler, Christian (Proceedings of the 20th International Symposium on Stabilization, Safety, and Security of Distributed Systems (SSS))
We extend the concept of monotonic searchability~\cite{DBLP:conf/opodis/ScheidelerSS15}~\cite{DBLP:conf/wdag/ScheidelerSS16} for self-stabilizing systems from one to multiple dimensions. A system is self-stabilizing if it can recover to a legitimate state from any initial illegal state. These kind of systems are most often used in distributed applications. Monotonic searchability provides guarantees when searching for nodes while the recovery process is going on. More precisely, if a search request started at some node $u$ succeeds in reaching its destination $v$, then all future search requests from $u$ to $v$ succeed as well. Although there already exists a self-stabilizing protocol for a two-dimensional topology~\cite{DBLP:journals/tcs/JacobRSS12} and an universal approach for monotonic searchability~\cite{DBLP:conf/wdag/ScheidelerSS16}, it is not clear how both of these concepts fit together effectively. The latter concept even comes with some restrictive assumptions on messages, which is not the case for our protocol. We propose a simple novel protocol for a self-stabilizing two-dimensional quadtree that satisfies monotonic searchability. Our protocol can easily be extended to higher dimensions and offers routing in $\mathcal O(\log n)$ hops for any search request.

Towards software-based tools for business model development: Using external stimuli for business model idea generation - Szopinski, Daniel (Bosch Business Model Innovation Summit 2018)

A Peer-to-Peer based Cloud Storage supporting orthogonal Range Queries of arbitrary Dimension - Benter, Markus; Knollmann, Till; Meyer auf der Heide, Friedhelm; Setzer, Alexander; Sundermeier, Jannik (Proceedings of the 4th International Symposium on Algorithmic Aspects of Cloud Computing (ALGOCLOUD))
We present a peer-to-peer network that supports the efficient processing of orthogonal range queries $R=\bigtimes_{i=1}^{d}[a_i,\,b_i]$ in a $d$-dimensional point space.\\ The network is the same for each dimension, namely a distance halving network like the one introduced by Naor and Wieder (ACM TALG'07). We show how to execute such range queries using $\mathcal{O}\left(2^{d'}d\,\log m + d\,|R|\right)$ hops (and the same number of messages) in total. Here $[m]^d$ is the ground set, $|R|$ is the size and $d'$ the dimension of the queried range. Furthermore, if the peers form a distributed network, the query can be answered in $\mathcal{O}\left(d\,\log m + d\,\sum_{i=1}^{d}(b_i-a_i+1)\right)$ communication rounds. Our algorithms are based on a mapping of the Hilbert Curve through $[m]^d$ to the peers.
Keywords: Distributed Storage; Multi-Dimensional Range Queries; Peer-to-Peer; Hilbert Curve

Flexible Ambiguity Resolution and Incompleteness Detection in Requirements Descriptions via an Indicator-based Configuration of Text Analysis Pipelines - Bäumer, Frederik Simon; Geierhos, Michaela (Proceedings of the 51st Hawaii International Conference on System Sciences)
Natural language software requirements descriptions enable end users to formulate their wishes and expectations for a future software product without much prior knowledge in requirements engineering. However, these descriptions are susceptible to linguistic inaccuracies such as ambiguities and incompleteness that can harm the development process. There is a number of software solutions that can detect deficits in requirements descriptions and partially solve them, but they are often hard to use and not suitable for end users. For this reason, we develop a software system that helps end-users to create unambiguous and complete requirements descriptions by combining existing expert tools and controlling them using automatic compensation strategies. In order to recognize the necessity of individual compensation methods in the descriptions, we have developed linguistic indicators, which we present in this paper. Based on these indicators, the whole text analysis pipeline is ad-hoc configured and thus adapted to the individual circumstances of a requirements description.
Keywords: Software Product Lines: Engineering; Services; and Management; Ambiguities; Incompleteness; Natural Language Processing; Software Requirements

Do Android taint analysis tools keep their promises? - Pauck, Felix; Bodden, Eric; Wehrheim, Heike (Proceedings of the 2018 26th ACM Joint Meeting on European Software Engineering Conference and Symposium on the Foundations of Software Engineering - ESEC/FSE 2018)

CrySL: An Extensible Approach to Validating the Correct Usage of Cryptographic APIs - Krüger, Stefan; Späth, Johannes; Ali, Karim; Bodden, Eric; Mezini, Mira (European Conference on Object-Oriented Programming (ECOOP))
Keywords: ITSECWEBSITE; CROSSING

Relays: A New Approach for the Finite Departure Problem in Overlay Networks - Scheideler, Christian; Setzer, Alexander (Proceedings of the 20th International Symposium on Stabilization, Safety, and Security of Distributed Systems (SSS 2018))
A fundamental problem for overlay networks is to safely exclude leaving nodes, i.e., the nodes requesting to leave the overlay network are excluded from it without affecting its connectivity. To rigorously study self-stabilizing solutions to this problem, the Finite Departure Problem (FDP) has been proposed [9]. In the FDP we are given a network of processes in an arbitrary state, and the goal is to eventually arrive at (and stay in) a state in which all leaving processes irrevocably decided to leave the system while for all weakly-connected components in the initial overlay network, all staying processes in that component will still form a weakly connected component. In the standard interconnection model, the FDP is known to be unsolvable by local control protocols, so oracles have been investigated that allow the problem to be solved [9]. To avoid the use of oracles, we introduce a new interconnection model based on relays. Despite the relay model appearing to be rather restrictive, we show that it is universal, i.e., it is possible to transform any weakly-connected topology into any other weakly-connected topology, which is important for being a useful interconnection model for overlay networks. Apart from this, our model allows processes to grant and revoke access rights, which is why we believe it to be of interest beyond the scope of this paper. We show how to implement the relay layer in a self-stabilizing way and identify properties protocols need to satisfy so that the relay layer can recover while serving protocol requests.

On Underlay-Aware Self-Stabilizing Overlay Networks - Götte, Thorsten; Scheideler, Christian; Setzer, Alexander (Proceedings of the 20th International Symposium on Stabilization, Safety, and Security of Distributed Systems (SSS 2018))
We present a self-stabilizing protocol for an overlay network that constructs the Minimum Spanning Tree (MST) for an underlay that is modeled by a weighted tree. The weight of an overlay edge between two nodes is the weighted length of their shortest path in the tree. We rigorously prove that our protocol works correctly under asynchronous and non-FIFO message delivery. Further, the protocol stabilizes after O(N^2) asynchronous rounds where N is the number of nodes in the overlay.

Maintaining vs. Milking Good Reputation when Customer Feedback is Inaccurate - Mir Djawadi, Behnud; Fahr, Rene; Haake, Claus-Jochen; Recker, Sonja (PLoS ONE)
In Internet transactions, customers and service providers often interact once and anonymously. To prevent deceptive behavior a reputation system is particularly important to reduce information asymmetries about the quality of the offered product or service. In this study we examine the effectiveness of a reputation system to reduce information asymmetries when customers may make mistakes in judging the provided service quality. In our model, a service provider makes strategic quality choices and short-lived customers are asked to evaluate the observed quality by providing ratings to a reputation system. The customer is not able to always evaluate the service quality correctly and possibly submits an erroneous rating according to a predefined probability. Considering reputation profiles of the last three sales, within the theoretical model we derive that the service provider’s dichotomous quality decisions are independent of the reputation profile and depend only on the probabilities of receiving positive and negative ratings when providing low or high quality. Thus, a service provider optimally either maintains a good reputation or completely refrains from any reputation building process. However, when mapping our theoretical model to an experimental design we find that a significant share of subjects in the role of the service provider deviates from optimal behavior and chooses actions which are conditional on the current reputation profile. With respect to these individual quality choices we see that subjects use milking strategies which means that they exploit a good reputation. In particular, if the sales price is high, low quality is delivered until the price drops below a certain threshold, and then high quality is chosen until the price increases again.

Patterns of Store-oriented Software Ecosystems: Detection, Classification, and Analysis of Design Options - Jazayeri, Bahar; Zimmermann, Olaf; Küster, Jochen; Engels, Gregor; Kundisch, Dennis; Szopinski, Daniel (The Latin American Conference on Pattern Languages of Programs (SLPLoP))
Software companies nowadays create ecosystems of users and third-party providers around their platforms. They often provide online stores so that the third-party developments can be exposed to users directly. The resulting ecosystems differ significantly from each other in their architectural designs because their providers differ in terms of business goals and contexts. Until now, this architectural diversity and rationale behind it are not well-understood. Therefore, it is not clear which software features contribute to ecosystem’s success with respect to certain business goals and context. This hinders systematic creation of ecosystems in the future. Thus, decision-making becomes too risky; for future ecosystem providers, which may lead to creation of inefficient ecosystems that lack critical features, and for third-party providers to rely on ad-hoc choices while deciding on suitability of an ecosystem for their future career. In this paper, we introduce three design patterns for store- oriented software ecosystems by classifying the design decisions, business goals, and context of 111 store-oriented software ecosystems. Each design pattern provides an architectural solution to achieve a different business goal while supporting a different context. We discuss how the design patterns are applied together in order to achieve more business goals. Our work supports ecosystem and third-party providers by sharing practice-proven architectural solutions, helping them to take informed architectural decisions and reduce technical risks.

A Highly Accurate Energy Model for Task Execution on Heterogeneous Compute Nodes - Lösch, Achim; Platzner, Marco (2018 IEEE 29th International Conference on Application-specific Systems, Architectures and Processors (ASAP))

A Prototyping Platform to Validate and Verify Network Service Header-based Service Chains - Peuster, Manuel; Schneider, Stefan Balthasar; Christ, Frederic; Karl, Holger (IEEE Conference on Network Function Virtualisation and Software Defined Networks (NFV-SDN) 5GNetApp)

Congestion games with mixed objectives - Feldotto, Matthias; Leder, Lennart; Skopalik, Alexander (Journal of Combinatorial Optimization)
We study a new class of games which generalizes congestion games andits bottleneck variant. We introduce congestion games with mixed objectives to modelnetwork scenarios in which players seek to optimize for latency and bandwidths alike.We characterize the (non-)existence of pure Nash equilibria (PNE), the convergenceof improvement dynamics, the quality of equilibria and show the complexity of thedecision problem. For games that do not possess PNE we give bounds on the approx-imation ratio of approximate pure Nash equilibria.

Trade-offs in Dynamic Resource Allocation in Network Function Virtualization - Schneider, Stefan Balthasar; Dräxler, Sevil; Karl, Holger (IEEE Global Communications Conference (GLOBECOM 2018))
Dynamic allocation of resources is a key feature in network function virtualization (NFV), enabling flexible adjustment of slices and contained network services to ever-changing service demands. Considering resource allocation across the entire network, many authors have proposed approaches to optimize the placement and chaining of virtual network function (VNF) instances and the allocation of resources to these VNF instances. In doing so, various optimization objectives are conceivable, e.g., minimizing certain required resources or the end-to-end delay of the placed services. In this paper, we investigate the relationship between four typical optimization objectives when coordinating the placement and resource allocation of chained VNF instances. We observe an interesting trade-off between minimizing the overhead of starting/stopping VNF instances and all other objectives when adapting to changed service demands.

A Generic Emulation Framework for Reusing and Evaluating VNF Placement Algorithms - Schneider, Stefan Balthasar; Peuster, Manuel; Karl, Holger (IEEE Conference on Network Function Virtualization and Software Defined Networks (NFV-SDN 2018))
In recent years, a variety of different approaches have been proposed to tackle the problem of scaling and placing network services, consisting of interconnected virtual network functions (VNFs). This paper presents a placement abstraction layer (PAL) that provides a clear and simple northbound interface for using such algorithms while hiding their internal functionality and implementation. Through its southbound interface, PAL can connect to different back ends that evaluate the calculated placements, e.g., using simulations, emulations, or testbed approaches. As an example for such evaluation back ends, we introduce a novel placement emulation framework (PEF) that allows executing calculated placements using real, containerbased VNFs on real-world network topologies. In a case study, we show how PAL and PEF facilitate reusing and evaluating placement algorithms as well as validating their underlying models and performance claims.

A Fully Integrated Multi-Platform NFV SDK - Schneider, Stefan Balthasar; Peuster, Manuel; Tavernier, Wouter; Karl, Holger (IEEE Conference on Network Function Virtualization and Software Defined Networks (NFV-SDN 2018))
A key challenge of network function virtualization (NFV) is the complexity of developing and deploying new network services. Currently, development requires many manual steps that are time-consuming and error-prone (e.g., for creating service descriptors). Furthermore, existing management and orchestration (MANO) platforms only offer limited support of standardized descriptor models or package formats, limiting the re-usability of network services. To this end, we introduce a fully integrated, open-source NFV service development kit (SDK) with multi-MANO platform support. Our SDK simplifies many NFV service development steps by offering initial generation of descriptors, advanced project management, as well as fully automated packaging and submission for on-boarding. To achieve multi-platform support, we present a package format that extends ETSI’s VNF package format. In this demonstration, we present the end-to-end workflow to develop an NFV service that is then packaged for multiple platforms, i.e., 5GTANGO and OSM.

Validity of Software Verification Results on Approximate Hardware - Isenberg, Tobias; Jakobs, Marie-Christine; Pauck, Felix; Wehrheim, Heike (IEEE Embedded Systems Letters)
Approximate computing (AC) is an emerging paradigm for energy-efficient computation. The basic idea of AC is to sacrifice high precision for low energy by allowing hardware to carry out “approximately correct” calculations. This provides a major challenge for software quality assurance: programs successfully verified to be correct might be erroneous on approximate hardware. In this letter, we present a novel approach for determining under what conditions a software verification result is valid for approximate hardware. To this end, we compute the allowed tolerances for AC hardware from successful verification runs. More precisely, we derive a set of constraints which—when met by the AC hardware—guarantees the verification result to carry over to AC. On the practical side, we furthermore: 1) show how to extract tolerances from verification runs employing predicate abstraction as verification technology and 2) show how to check such constraints on hardware designs. We have implemented all techniques, and exemplify them on example C programs and a number of recently proposed approximate adders.

Towards explaining the popularity of the Business Model Canvas: A dual coding approach - John, Thomas; Szopinski, Daniel (Proceedings of the Multikonferenz Wirtschaftsinformatik 2018 (MKWI), Lüneburg, Germany)

Platform Launch Strategies - Stummer, Christian; Kundisch, Dennis; Decker, Reinhold (Business & Information Systems Engineering)

When Local Praise Becomes Cheap Talk - Analyzing the Relationship between Reviewer Location and Usefulness of Online Reviews - Neumann, Jürgen; Gutt, Dominik; Kundisch, Dennis; van Straaten, Dirk (Proceedings of the Multikonferenz Wirtschaftsinformatik 2018 (MKWI), Lüneburg, Germany)
With a growing number of online reviews, it becomes increasingly important for customers and online review platforms to find groups of reviewers who write useful reviews. Customers who review local offline businesses such as restaurants can identify themselves as locals or travelers and thus implicitly assign themselves to a specific reviewer group. This study investigates the relationship between identifying as a local and the perceived usefulness of their online reviews. Using data from Yelp.com, we empirically test hypotheses derived from attribution theory. Our results suggest that neutral and negative reviews by locals tend to be perceived as more useful than reviews by travelers. Positive reviews by locals, however, are not perceived as more useful. These findings provide significant practical implications for online review platforms and local offline businesses.

Sorting Out the Lemons - Identifying Product Failures in Online Reviews and their Relationship with Sales - Gutt, Dominik (Proceedings of the Multikonferenz Wirtschaftsinformatik 2018 (MKWI), Lüneburg, Germany)
It is well-established that both average online ratings and the number of ratings positively impact product sales. Yet, the economic implications of the information contained in the online review texts is not that well understood. In this study, we contribute to the understanding of online review texts and its economic implications by conducting and validating an unsupervised machine learning algorithm, the latent dirichlet allocation, to identify online reviews that mention product failures. Furthermore, we show that the textual information on product failures are associated with lower product sales. Our results help online review system designers, e.g., amazon, to identify these reviews and to make them easily accessible to potential customers to support the customer’s purchasing decision. Academics can build on our results by applying our validated topic identification strategy and by linking reviews mentioning product failure to a range of different outcomes.

More than skills: A novel matching proposal for multiplayer video games - Stroh-Maraun, Nadja; Kaimann, Daniel; Cox, Joe (Entertainment Computing)

Decomposing the Variance of Consumer Ratings and the Impact on Price and Demand - Zimmermann , Steffen; Herrmann, Philipp; Kundisch, Dennis; Nault, Barry (Information Systems Research)
Consumer ratings play a decisive role in purchases by online shoppers. Although the effect of the average and the number of consumer ratings on future product pricing and demand have been studied with some conclusive results, the effects of the variance of these ratings are less well understood. We develop a model which considers durable goods that are characterized by three types of attributes: search attributes, experience attributes, and transformed attributes the latter are conventional experience attributes that are transformed by consumer ratings into attributes that can be searched. Using informed search attributes to refer to the combination of search attributes and transformed attributes, we consider two sources of variance of consumer ratings: taste differences about informed search attributes and quality differences in the form of product failure representing experience attributes. We find that (i) optimal price increases and demand decreases in variance caused by informed search attributes, (ii) optimal price and demand decrease in variance caused by experience attributes, and (iii) by holding the average rating as well as the total variance constant, for products with low total variance price and demand increase in the relative share of variance caused by informed search attributes. Counter to intuition, we demonstrate that risk averse consumers may prefer a higher priced product with a higher variance in ratings when deciding between two similar products with the same average rating. Finally, our model provides a theoretical explanation for the empirically observed j-shaped distribution of consumer ratings in e-commerce that differs from established explanations.

Reducer-Based Construction of Conditional Verifiers - Beyer, Dirk; Jakobs, Marie-Christine; Lemberger, Thomas; Wehrheim, Heike (Proceedings of the 40th International Conference on Software Engineering (ICSE))
to appear

Unschärfe bei der Interpretation natürlichsprachlicher Anforderungsbeschreibungen - Geierhos, Michaela (Unschärfe - Der Umgang mit fehlender Eindeutigkeit)
Präzision ist kein Zufall. Sie wird vom Menschen herbeigeführt, indem Übereinstimmung mit einem Standard oder einem akzeptierten Wert angestrebt wird oder die Reproduzierbarkeit von Experimenten möglichst hoch sein muss. Was aber tun, wenn Präzision mangels verfügbarer Informationen nicht hergestellt werden kann? Wie gehen Wissenschaft und Kunst dann mit dieser fehlenden Eindeutigkeit um? Die Autorinnen und Autoren dieses Sammelbandes beleuchten aus der Perspektive ihrer jeweiligen Fachdisziplin die Chancen bei der Berücksichtigung von Unschärfe(n) in ihrer Forschung und Kunst. Denn Unschärfe ist Realität.

Beschreib mir deine Wohnung und ich sag dir wer du bist - Eine explorative Analyse von Gastgeberpersönlichkeiten auf Airbnb - Müller, Michelle; Gutt, Dominik; Neumann, Jürgen (Multikonferenz Wirtschaftsinformatik (MKWI) 2018)

A Duration Model Analysis of Consumer Preferences and Determinants of Video Game Consumption - Kaimann, Daniel; Stroh-Maraun, Nadja; Cox, Joe (Journal of Consumer Behaviour)

How to Deal with Inaccurate Service Requirements? Insights in Our Current Approach and New Ideas - Bäumer, Frederik Simon; Geierhos, Michaela (Joint Proceedings of REFSQ-2018 Workshops, Doctoral Symposium, Live Studies Track, and Poster Track co-located with the 23rd International Conference on Requirements Engineering: Foundation for Software Quality (REFSQ 2018))
The main idea in On-The-Fly Computing is to automatically compose existing software services according to the wishes of end-users. However, since user requirements are often ambiguous, vague and incomplete, the selection and composition of suitable software services is a challanging task. In this paper, we present our current approach to improve requirement descriptions before they are used for software composition. This procedure is fully automated, but also has limitations, for example, if necessary information is missing. In addition, and in response to the limitations, we provide insights into our above-mentioned current work that combines the existing optimization approach with a chatbot solution.

CORDULA: Software Requirements Extraction Utilizing Chatbot as Communication Interface - Friesen, Edwin; Bäumer, Frederik Simon; Geierhos, Michaela (Joint Proceedings of REFSQ-2018 Workshops, Doctoral Symposium, Live Studies Track, and Poster Track co-located with the 23rd International Conference on Requirements Engineering: Foundation for Software Quality (REFSQ 2018))
Natural language requirement descriptions are often unstructured, contradictory and incomplete and are therefore challenging for automatic processing. Although many of these deficits can be compensated by means of Natural Language Processing, there still remain cases where interaction with end-users is necessary for clarification. In this paper, we present our idea of using chatbot technology to establish end-user communication in order to support the automatic compensation of some deficits in natural language requirement descriptions.

Back to Basics: Extracting Software Requirements with a Syntactic Approach - Caron, Matthew; Bäumer, Frederik Simon; Geierhos, Michaela (Joint Proceedings of REFSQ-2018 Workshops, Doctoral Symposium, Live Studies Track, and Poster Track co-located with the 23rd International Conference on Requirements Engineering: Foundation for Software Quality (REFSQ 2018))
As our world grows in complexity, companies and employees alike need, more than ever before, solutions tailored to their exact needs. Since such tools cannot always be purchased off-the-shelf and need to be designed from the ground up, developers rely on software requirements. In this paper, we present our vision of a syntactic rule-based extraction tool for software requirements specification documents. In contrast to other methods, our tool will allow stakeholders to express their needs and wishes in unfiltered natural language, which we believe is essential for non-expert users.

A Note on Manipulability in School Choice with Reciprocal Preferences - Haake, Claus-Jochen; Stroh-Maraun, Nadja
We show that the Boston school choice mechanism (BM), the student proposing deferred acceptance algorithm (DA) and the top trading cycles algorithm (TTC) generate the same outcome when the colleges’ priorities are modified according to students’ preferences in a “first preferences first” manner. This outcome coincides with the BM outcome under original priorities. As a result, the DA and TTC mechanism that are non-manipulable under original priorities become vulnerable to strategic behavior.

Does Informational Equivalence Preserve Strategic Behavior? An Experimental Study on Trockel's Game - Duman, Papatya
The purpose of the present study is to experimentally test a version of the classical Chain Store Game (CSG) paradox, proposed by Trockel (1986), and determine whether one of the two theories of Induction and Deterrence, which were originally tested competitively by Selten (1978), may better account for the results. With complete and perfect information, the CSG of Selten (1978) was designed to analyze the role of reputation in repeated market interactions. Its results were discussed in two diﬀerent ways: one is based on backward induction, and the other is intuitively derived from a deterrence argument. As the two explanations are incompatible, alternative models have been proposed to understand them better. The alternative game proposed by Trockel is an imperfect information version of the CSG in which the order of the two players is changed in each round and the ’Out-Aggressive’ equilibrium is used to build reputation. The existence of more than one equilibrium is the basis for the building of reputation. To the best of my knowledge, this study is the ﬁrst attempt to experimentally test this alternative game with the same purpose.
Keywords: Chain Store Game; reputation building; entry deterrence; Trockel's game

Preemptive Repression: Deterrence, Backfiring, Iron Fists and Velvet Gloves - De Jaegher, Kris; Hoyer, Britta (Journal of Conflict Resolution)
We present a game-theoretic model of the repression–dissent nexus, focusing on preemptive repression. A small group of instigating dissidents triggers a protest if each dissident participates. The dissidents face random checks by security forces, and when an individual dissident is caught while preparing to participate, he or she is prevented from doing so. Each dissident can invest in countermeasures, which make checks ineffective. For large benefits of protest, higher preemptive repression in the form of a higher number of checks has a deterrence effect and makes dissidents less prone to invest in countermeasures, decreasing the probability of protest. For small benefits of protest, higher preemptive repression instead has a backfiring effect. Both myopic and farsighted governments avoid the backfiring effect by setting low levels of preemptive repression (velvet-glove strategy). However, only a farsighted government is able to exploit the deterrence effect by maintaining a high level of preemptive repression (iron-fist strategy).

Variety in the video game industry: An empirical study of the Wundt curve - Kaimann, Daniel; Stroh-Maraun, Nadja; Cox, Joe (Managerial and Decision Economics)

Pure Nash equilibria in restricted budget games - Drees, Maximilian; Feldotto, Matthias; Riechers, Sören; Skopalik, Alexander (Journal of Combinatorial Optimization)
In budget games, players compete over resources with finite budgets. For every resource, a player has a specific demand and as a strategy, he chooses a subset of resources. If the total demand on a resource does not exceed its budget, the utility of each player who chose that resource equals his demand. Otherwise, the budget is shared proportionally. In the general case, pure Nash equilibria (NE) do not exist for such games. In this paper, we consider the natural classes of singleton and matroid budget games with additional constraints and show that for each, pure NE can be guaranteed. In addition, we introduce a lexicographical potential function to prove that every matroid budget game has an approximate pure NE which depends on the largest ratio between the different demands of each individual player.

Learning to Flip the Bias of News Headlines - Chen, Wei-Fan; Wachsmuth, Henning; Al Khatib, Khalid; Stein, Benno (Proceedings of the 11th International Conference on Natural Language Generation)

A User Study on Snippet Generation: Text Reuse vs. Paraphrases - Chen, Wei-Fan; Hagen, Matthias; Stein, Benno; Potthast, Martin (Proceedings of the 41st International ACM SIGIR Conference on Research & Development in Information Retrieval)

A Plan for Ancillary Copyright: Original Snippets. - Potthast, Martin; Chen, Wei-Fan; Hagen, Matthias; Stein, Benno (Proceedings of the Second International Workshop on Recent Trends in News Information Retrieval)

Enhanced Security of Attribute-Based Signatures - Blömer, Johannes; Eidens, Fabian; Juhnke, Jakob (The International Conference on Cryptology And Network Security (CANS))

Delegatable Attribute-based Anonymous Credentials from Dynamically Malleable Signatures - Blömer, Johannes; Bobolz, Jan (ACNS 2018 Applied Cryptography & Network security)
In this paper, we introduce the notion of delegatable attribute-based anonymous credentials (DAAC). Such systems offer fine-grained anonymous access control and they give the credential holder the ability to issue more restricted credentials to other users. In our model, credentials are parameterized with attributes that (1) express what the credential holder himself has been certified and (2) define which attributes he may issue to others. Furthermore, we present a practical construction of DAAC. For this construction, we deviate from the usual approach of embedding a certificate chain in the credential. Instead, we introduce a novel approach for which we identify a new primitive we call dynamically malleable signatures (DMS) as the main ingredient. This primitive may be of independent interest. We also give a first instantiation of DMS with efficient protocols.

OpenCL-based FPGA Design to Accelerate the Nodal Discontinuous Galerkin Method for Unstructured Meshes - Kenter, Tobias; Mahale, Gopinath; Alhaddad, Samer; Grynko, Yevgen; Schmitt, Christian; Afzal, Ayesha; Hannig, Frank; Förstner, Jens; Plessl, Christian (Proc. Int. Symp. on Field-Programmable Custom Computing Machines (FCCM))
The exploration of FPGAs as accelerators for scientific simulations has so far mostly been focused on small kernels of methods working on regular data structures, for example in the form of stencil computations for finite difference methods. In computational sciences, often more advanced methods are employed that promise better stability, convergence, locality and scaling. Unstructured meshes are shown to be more effective and more accurate, compared to regular grids, in representing computation domains of various shapes. Using unstructured meshes, the discontinuous Galerkin method preserves the ability to perform explicit local update operations for simulations in the time domain. In this work, we investigate FPGAs as target platform for an implementation of the nodal discontinuous Galerkin method to find time-domain solutions of Maxwell's equations in an unstructured mesh. When maximizing data reuse and fitting constant coefficients into suitably partitioned on-chip memory, high computational intensity allows us to implement and feed wide data paths with hundreds of floating point operators. By decoupling off-chip memory accesses from the computations, high memory bandwidth can be sustained, even for the irregular access pattern required by parts of the application. Using the Intel/Altera OpenCL SDK for FPGAs, we present different implementation variants for different polynomial orders of the method. In different phases of the algorithm, either computational or bandwidth limits of the Arria 10 platform are almost reached, thus outperforming a highly multithreaded CPU implementation by around 2x.
Keywords: tet_topic_hpc